PERAN PERPUSTAKAAN DAN TENAGA PERPUSTAKAAN SEKOLAH/MADRASAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI SEKOLAH/MADRASAH - Dewi, Laksmi; Suhardini, Asep Dudi (Edulib, 2014)
AbstractThis paper begins with the emergence of problems in the implementation of education about the role of the school/madrasah library. Library as one of the important factor in improving the quality of the learning process in schools / madrasah. It is undeniable that the number of libraries and school/madrasah librarian are still below the average of national standard of library school/ madrasah. Required the intervention in enhancing the role of libraries and school library personnel / madrasah. Through training madrassa library management, training participants are expected to increase their ability after the training, particularly in carrying out his duties as a school library personnel. Based on the results of pre-test and post-test data showed that it had an increased knowledge of the trainees. The trainees also found the library management training has particular relevance and effectiveness in improving the understanding related to the management of the library. After training, the trainees also apply in libraries madrassas through improvements in the management of the library. Training library management has proven effective in improving knowledge, attitudes, and skills in carrying out the task of managing the library.Keyword: Library, school librarian, School quality improvementÂ AbstrakTulisan ini diawali dengan munculnya permasalahan dalam pelaksanaan pendidikan tentang peran perpustakaan sekolah/madrasah. Perpustakaan sebagai salah satu factor penting dalam meningkatkan kualitas proses pembelajaran di sekolah/madrasah. Tak dapat dipungkiri bahwa jumlah perpustakaan dan tenaga perpustakaan sekolah/madrasah masih berada di bawah rata-rata standar perpustakaan sekolah/madrasah yang telah ditetapkan oleh pemerintah. Diperlukan adanya intervensi dalam meningkatkan peran perpustakaan dan tenaga perpustakaan sekolah/ madrasah. Melalui pelatihan pengelolaan perpustakaan madrasah, peserta pelatihan diharapkan dapat meningkat kemampuannya setelah mengikuti pelatihan tersebut, khususnya dalam melaksanakan tugasnya sebagai tenaga perpustakaan sekolah. Berdasarkan hasil pre test dan post test diperoleh data bahwa secara pengetahuan peserta pelatihan memiliki peningkatan. Peserta pelatihan juga berpendapat bahwa pelatihan pengelolaan perpustakaan memiliki relevansi dan efektivitas khususnya dalam meningkatkan pemahamannya terkait pengelolaan perpustakaan. Setelah mengikuti pelatihan, peserta pelatihan pun menerapkannya di pepustakaan madrasahnya melalui pembenahan dalam pengelolaan perpustakaan. Pelatihan pengelolaan perpustakaan terbukti efektif memberikan peningkatan pengetahuan, sikap, dan keterampilannya dalam melaksanakan tugas mengelola perpustakaan.Keyword: Perpustakaan, Tenaga Perpustakaan, Kualitas Pendidikan Madrasah